Effects of interruptions of external beam radiation therapy on outcomes in patients with prostate cancer. Issue 1 (13th October 2017) - Dong, Yanqun; Zaorsky, Nicholas G; Li, Tianyu; Churilla, Thomas M; Viterbo, Rosalia; Sobczak, Mark L; Smaldone, Marc C; Chen, David YT; Uzzo, Robert G; Hallman, Mark A; Horwitz, Eric M
Abstract: Introduction: To evaluate if interruptions of external beam radiation therapy impact outcomes in men with localized prostate cancer (PCa). Methods: We included men with localized PCa treated with three‐dimensional conformal radiotherapy (3D‐CRT) or intensity‐modulated radiation therapy (IMRT) of escalated dose (≥74 Gy in 1.8 or 2 Gy fractions) between 1992 and 2013 at an NCI‐designated cancer centre. Men receiving androgen deprivation therapy were excluded. The non‐treatment day ratio (NTDR) was defined as the number of non‐treatment days divided by the total elapsed days of therapy. NTDR was analysed for each National Comprehensive Cancer Network (NCCN) risk group. Results: There were 1728 men included (839 low‐risk, 776 intermediate‐risk and 113 high‐risk), with a median follow up of 53.5 months (range 12–185.8). The median NTDR was 31% (range 23–71%), translating to approximately 2 breaks (each break represents a missed treatment that will be made up) for 8 weeks of RT with 5 treatments per week. The 75 percentile of NTDR was 33%, translating to approximately 4 breaks, which was used as the cutoff for analysis. There were no significant differences in freedom from biochemical failure, freedom from distant metastasis, cancer specific survival, or overall survival for men with NTDR ≥33% compared to NTDR<33% for each risk group. Multivariable analyses including NTDR, age, race, Gleason score, T stage, and PSA were performed using the proportional hazards regression procedure. NTDR≥33% was not significantly associated with increased hazard ratio for outcomes in each risk group compared to NTDR<33%. Conclusion: Unintentional treatment breaks during dose escalated external beam radiation therapy for PCa did not cause a significant difference in outcomes, although duration of follow up limits the strength of this conclusion.